A case study of gust factor of a strong typhoon. Issue 138 (March 2015) - Cao, Shuyang; Tamura, Yukio; Kikuchi, Naoshi; Saito, Mamoru; Nakayama, Ikuo; Matsuzaki, Yutaka
Abstract: This paper studied the gust factor associated with a very strong typhoon (Typhoon Maemi 2003), whose maximum 10 min mean wind speed was greater than 60 m/s. The wind speed was recorded by multiple sonic and vane anemometers near the seashore of an island. Only stationary wind speed samples are analyzed to obtain the gust factor. The study focuses on the dependences of gust factor on gust averaging time, sample duration, and mean wind speed during the typhoon's passage. The results suggest that typhoon gust factors have no significant difference from those associated with non-typhoon winds, and can be described using models developed for standard neutral boundary layer flow conditions.